One-time application of biochar influenced crop yield across three cropping cycles on tropical sandy loam soil in Ghana. Issue 2 (February 2021) - Frimpong, Kwame Agyei; Phares, Christian Adler; Boateng, Isaac; Abban-Baidoo, Emmanuel; Apuri, Lenin
Abstract: The preparation and application of biochar by smallholder farmers is labour intensive hence an effective one-time application for multiple cropping seasons would be desirable by farmers and researchers. In this study, one-time biochar application as a soil amendment and its interaction with compost and NPK on yield performances of different crops was investigated across three cropping seasons. Treatments included biochar applied alone or together with compost, inorganic NPK fertilizer or both. Maize, okra and cassava were planted in succession and data was collected on their shoot N, P and K concentrations, yields as well as selected soil parameters (pH, exchangeable acidity, total exchangeable bases, effective cation exchange capacity, total N, total organic carbon, available phosphorus). Data was analyzed with GenSTAT and results were presented in tables and bar graph. Corn cob biochar applied solely did not significantly improve maize and okra yield in the first and second cropping season but increased yield of cassava significantly at the third cropping season. Yield increased in sole NPK, compost and NPK + compost treatments for all cropping cycles, but yields obtained from these treatments in the presence of biochar were greater than their corresponding treatments without biochar. The study also showed that biochar application together with compost, NPK or both, improved total organic carbon, total nitrogen, available phosphorus, total exchangeable bases, exchangeable acidity, effective cation exchange capacity and pH as well as tissue N, P and K of all crops. Our findings demonstrated that a single application of biochar, particularly in the presence of compost, inorganic NPK fertilizer or both can increase yields across three cropping seasons and improve soil fertility. Abstract : Biochar, NPK fertilizer, compost, yield